2020
DOI: 10.1038/s41598-020-64226-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor promotes healthy microbial metabolites and microbiome

Abstract: Microbiota derived metabolites act as chemical messengers that elicit a profound impact on host physiology. Vitamin D receptor (VDR) is a key genetic factor for shaping the host microbiome. However, it remains unclear how microbial metabolites are altered in the absence of VDR. We investigated metabolites from mice with tissue-specific deletion of VDR in intestinal epithelial cells or myeloid cells. Conditional VDR deletion severely changed metabolites specifically produced from carbohydrate, protein, lipid, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 47 publications
0
57
0
Order By: Relevance
“…37 Conditional VDR deletion severely changed metabolites specifically produced from carbohydrate, protein, lipid, and bile acid metabolism. 37 In the future, we will study VDR in immune cells during cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…37 Conditional VDR deletion severely changed metabolites specifically produced from carbohydrate, protein, lipid, and bile acid metabolism. 37 In the future, we will study VDR in immune cells during cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…It may be further implicated in the GMB axis of neurologic disorders. Deletion of intestinal epithelial VDR increased kynurenine, a pathway associated with inflammatory neurological disorder in a mouse model [ 144 ]. Our recent study has also shown that the mice with VDR deletion in immune cells displayed significant downregulation of quinolinate and tocopherol pathway-derived metabolites and increase in nicotinamide.…”
Section: Microbial Metabolite In Autism Spectrum Disorder and Attentimentioning
confidence: 99%
“…These changes indicate a potential role of VDR in neurophysiology. The role of vitamin D/VDR in gut–brain axis needs further investigation in future research [ 144 ].…”
Section: Microbial Metabolite In Autism Spectrum Disorder and Attentimentioning
confidence: 99%
“…There is also evidence that probiotics play a role in these modulations. Our recent study has shown that VDR promotes healthy microbial metabolites and microbiome in a tissue specific and gender specific manner [149]. However, more studies are necessary to elucidate this influence and all the metabolic steps associated.…”
Section: Probiotic Role Regulated By Vitamin D/vdrmentioning
confidence: 98%
“…In addition to microbiome regulation, long chain acylcarnitines (LCACs), tocopherol, and equol metabolisms were also influenced by VDR function and HFD. Thus, it can be concluded that both, diet and VDR status, play a role in metabolic diseases, inflammation, risk of colon cancer, and epigenetic pathways [149].…”
Section: Probiotic Role Regulated By Vitamin D/vdrmentioning
confidence: 99%